2008
DOI: 10.1124/jpet.108.141085
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CXCL12/CXCR4 Axis Ameliorates Murine Experimental Colitis

Abstract: Recent studies indicate that the CXCL12/CXCR4 interaction is involved in several inflammatory conditions. However, it is unclear whether this interaction has a role in the pathophysiology of inflammatory bowel disease (IBD). We investigated the significance of this interaction in patients with IBD and in mice with dextran sulfate sodium (DSS)-induced colitis and the effect of a CXCR4 antagonist on experimental colitis. First, we measured CXCR4 expression on peripheral T cells in patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 40 publications
4
84
0
Order By: Relevance
“…We studied protein expression and observed a regional expression pattern of CXCL12 protein in Crohn's disease showing marked up-regulation in areas of ulceration and erosion compared with normal colon. Very recently, CXCR4 expression was evaluated on peripheral T cells in patients with inflammatory bowel disease; CXCR4 immunofluorescence was significantly higher in patients with active ulcerative colitis compared with normal controls (60). CXCR4 expression levels of ulcerative colitis patients also correlated with disease activity, suggesting that the CXCL12-CXCR4 axis is involved in the inflammatory process in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied protein expression and observed a regional expression pattern of CXCL12 protein in Crohn's disease showing marked up-regulation in areas of ulceration and erosion compared with normal colon. Very recently, CXCR4 expression was evaluated on peripheral T cells in patients with inflammatory bowel disease; CXCR4 immunofluorescence was significantly higher in patients with active ulcerative colitis compared with normal controls (60). CXCR4 expression levels of ulcerative colitis patients also correlated with disease activity, suggesting that the CXCL12-CXCR4 axis is involved in the inflammatory process in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 expression levels of ulcerative colitis patients also correlated with disease activity, suggesting that the CXCL12-CXCR4 axis is involved in the inflammatory process in these patients. Indeed, blockade of the CXCL12-CXCR4 axis ameliorated murine experimental colitis (60). We hypothesized that, in view of the coexpression of CXCL12 and PAD in Crohn's disease and the evidence that chemokines are substrates for PAD (24,25), also crucial NH 2 -terminal arginine residues in CXCL12 might be converted by this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in IBD, CXCL12 was significantly up-regulated in the inflamed compared to the non-inflamed epithelium and stronger expression of CXCL12 in intestinal tissues was observed in patients with UC than in those with CD. Thus, this expression was likely to be more specific in active UC patients than in CD patients, However, using CXCL12/GFP knock-in approach, Mikami, et al revealed that CXCL12-expressing cells were mainly observed in the perivascular sites of the normal colonic mucosa, suggesting that the CXCL12-expressing cells were morphologically considered to be pericytes (adjacent to the endothelial cell) but not epithelial cells (30). After DSS administration, gene expression of CXCL12 was strongly induced in mice with DSScolitis, which was compatible to human IBD data reported by Dotan.…”
Section: How Is Cxcl12/cxcr4 Axis Involved In the Pathophysiology Of mentioning
confidence: 99%
“…Mikami, et al investigated the role of CXCL12/CXCR4 axis in patents with IBD by analysis of CXCR4 expression on peripheral T cells (30). They demonstrated that CXCR4 expression on peripheral T cells in patients with active UC was significantly higher than that in inactive UC and controls.…”
Section: How Is Cxcl12/cxcr4 Axis Involved In the Pathophysiology Of mentioning
confidence: 99%
See 1 more Smart Citation